Territórios de vida e de esperança nos acampamentos Fortaleza e Renascer na Mesorregião Sudeste, Mato Grosso - Miyashiro, Shirlei Fernandes de Oliveira (2015)
This research presents some discussions based on the logic of the organization of the camps of landless, understood as a place of resistance, that is, the reactivation of the actions of these rural workers. The discourse on the social organization of the camps have been a concern of several segments, disciplines and government agencies or not. They were visited and mapped the Fortaleza camps in the city of Guiratinga and Renascer in the city of Pedra Preta, both located in the southeastern region of the state of Mato Grosso, where it was applied a questionnaire that sought to identify the camp's profile and understand the logic of flows of people, even living in the camp, establishes certain mobility between rural and urban. Of the 18 respondents, 10 (55.5%) reside constantly in the camp, while 8 (44.4%) are itinerant. In this light 15 (83.3%) agree with this flow, mainly by the need to work; the minimum income from activities in the camp and to improve quality of life. In this perspective the camp appears as a temporary territory, ie a territory of life and hope, which seeks the achievement of the settlement, the social transformation.